Aging in rural places : policies, programs, and professional practice - Hash, Kristina Michelle; Jurkowski, Elaine Theresa; Krout, John A. (Springer Publishing Company, LLC, 2015)
Research documents that rural elders are poorer, live in less adequate housing, and have far fewer health and service options available to them than their urban counterparts, yet there is a critical lack of current and detailed information on the problems facing rural elders and on the professional practices that serve this population. This text fills this gap by introducing readers to rural areas and their residents and discussing the issues, programs, and policies designed to meet their needs. Through a multidisciplinary lens, it examines and defines specific competencies required for succes.